Mouse Models of Familial Hemiplegic Migraine for Studying Migraine Pathophysiology - Dehghani, Anisa (Curr Neuropharmacol, 2019)
Migraine, an extremely disabling neurological disorder, has a strong genetic component. Since monogenic mi-graines (resulting from mutations or changes in a single gene) may help researchers discover migraine pathophysiology, transgenic mice models harboring gene mutations identified in Familial Hemiplegic Migraine (FHM) patients have been gen-erated. Studies in these FHM mutant mice models have shed light on the mechanisms of migraine and may aid in the identifi-cation of novel targets for treatment. More specifically, the studies shed light on how gene mutations, hormones, and other factors impact the pathophysiology of migraine. The models may also be of relevance to researchers outside the field of mi-graine as some of their aspects are relevant to pain in general. Additionally, because of the comorbidities associated with mi-graine, they share similarities with the mutant mouse models of epilepsy, stroke, and perhaps depression. Here, we review the experimental data obtained from these mutant mice and focus on how they can be used to investigate the pathophysiology of migraine, including synaptic plasticity, neuroinflammation, metabolite alterations, and molecular and behavioral mecha-nisms of pain.